2023
DOI: 10.1038/s41467-023-39920-5
|View full text |Cite
|
Sign up to set email alerts
|

ARIH1 activates STING-mediated T-cell activation and sensitizes tumors to immune checkpoint blockade

Abstract: Despite advances in cancer treatment, immune checkpoint blockade (ICB) only achieves complete response in some patients, illustrating the need to identify resistance mechanisms. Using an ICB-insensitive tumor model, here we discover cisplatin enhances the anti-tumor effect of PD-L1 blockade and upregulates the expression of Ariadne RBR E3 ubiquitin-protein ligase 1 (ARIH1) in tumors. Arih1 overexpression promotes cytotoxic T cell infiltration, inhibits tumor growth, and potentiates PD-L1 blockade. ARIH1 mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…Therefore, candidate compounds should be carefully selected and validated. To be noted, the validation rate for miR-132 inducers was comparable to other recently published small compound screens [60][61][62] .…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, candidate compounds should be carefully selected and validated. To be noted, the validation rate for miR-132 inducers was comparable to other recently published small compound screens [60][61][62] .…”
Section: Discussionsupporting
confidence: 64%
“… 217 STING agonists have also been found to sensitize tumors to immune checkpoint inhibitors. 218 This discovery suggests a synergistic potential where activating the STING pathway can enhance the effectiveness of treatments that target immune checkpoints.…”
Section: Innate Immune Pathways In Cancermentioning
confidence: 99%
“… 371 , 372 Additionally, the effectiveness of ICBs depends on the sufficient expression of corresponding receptors on target cells, and innate immune pathway agonists can upregulate the expression of these molecules. 218 , 220 , 499 , 524 …”
Section: Cancer Therapeutic Strategies Targeting Innate Immune Pathwaymentioning
confidence: 99%
“…Moreover, Bruand et al 51 have revealed that the elimination of endogenous STING in tumors decreases neoangiogenesis, augments CD8 + T cell infiltration, and reverses resistance to dual immune checkpoint blockade therapy. Ariadne RBR E3 ubiquitin protein ligase 1 (Arih1) mediates the ubiquitination and degradation of DNA PKcs, and consequently triggers STING pathway activation, promotes the infiltration of cytotoxic T cells, inhibits tumor growth, and renders tumors sensitive to PD-L1 blockade 52 . The nuclear receptor Rev-erb alpha (NR1D1) fosters the accumulation of cytoplasmic DNA fragments induced by DNA damage, and subsequently activates the cGAS-STING signaling pathway.…”
Section: The Cgas-sting Pathway In Cancer Biologymentioning
confidence: 99%